2020
DOI: 10.11152/mu-2200
|View full text |Cite
|
Sign up to set email alerts
|

Application value of real-time shear wave elastography in differential diagnosis of testicular torsion

Abstract: Aim: To evaluate the clinical value of real-time shear wave elastography (SWE) in differential diagnosis of testicular torsion and acute orchiditis.Material and methods: During a 3-year period, 14 cases of testicular torsion and 16 cases of acute orchiditis met the inclusion criteria. Young’s modulus maximum hardness (Emax) of testicular capsule region, middle testicular parenchyma, warped spermatic segment or inferior spermatic segment was measured in each group. SWE “stiff ring sign” of testis refers to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…SWE permits quantitative evaluation of tissue hardness in a noninvasive manner by way of Young’s modulus, an objective measure of elasticity [ 22 ]. The higher the Young’s modulus is, the harder the tissue [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…SWE permits quantitative evaluation of tissue hardness in a noninvasive manner by way of Young’s modulus, an objective measure of elasticity [ 22 ]. The higher the Young’s modulus is, the harder the tissue [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the differential diagnosis between inflammatory pathology and testicular torsion, higher SWE values have been found in the latter when assessing the spermatic cord and testicular capsule, while no significant difference was found in testicular parenchyma stiffness 47 …”
Section: Discussionmentioning
confidence: 96%
“…In the differential diagnosis between inflammatory pathology and testicular torsion, higher SWE values have been found in the latter when assessing the spermatic cord and testicular capsule, while no significant difference was found in testicular parenchyma stiffness. 47 In focal lesions several studies have constantly found that neoplasms demonstrate higher stiffness using both SWE and SE; a soft pattern was however detected in some cases. Pedersen et al also discovered a correlation between SWE and MRI-DWI values, meaning that within stiff lesions a higher impediment to water molecules diffusion is present.…”
Section: Discussionmentioning
confidence: 99%
“…In the first part, we observed the changes in pathology and SWE of a thrombus over time and changes to the contrast medium entering the thrombus over time through in vitro experiments; this was done to determine whether or not contrast agent entering a thrombus changes with the hardness. SWE has been proved to be able to quantitatively evaluate tissue hardness in a noninvasive way by obtaining the Young's modulus of the corresponding part, which objectively reflects its elasticity [21]. The higher the Young's modulus, the harder the tissue [7].…”
Section: Discussionmentioning
confidence: 99%